Barriers, Springboards and Benchmarks: China Conceptualizes the Pacific "Island Chains"*. (21st January 2016) - Erickson, Andrew S.; Wuthnow, Joel
Abstract: US government reports describe Chinese-conceived "island chains" in the Western Pacific as narrow demarcations for Chinese "counter-intervention" operations to defeat US and allied forces in altercations over contested territorial claims. The sparse scholarship available does little to contest this excessively myopic assertion. Yet, further examination reveals meaningful differences that can greatly enhance an understanding of Chinese views of the "island chains" concept, and with it important aspects of China's efforts to develop as a maritime power. Long before China had a navy or naval strategists worthy of the name, the concept had originated and been developed for decades by previous great powers vying for Asia-Pacific influence. Today, China's own authoritative interpretations are flexible, nuanced and multifaceted – befitting the multiple and sometimes contradictory factors with which Beijing must contend in managing its meteoric maritime rise. These include the growing importance of sea lane security at increasing distances and levels of operational intensity. 摘要: 美国政府报告把中国设想的西太平洋 "岛链" 概念描述为中国军队为在有关领土争端的 "反干涉"作战中试图打败美国和盟国部队而设立的狭窄的界线。寥寥无几的相关研究对这个过于短视的看法也没有提出不同意见。然而, 进一步的分析却发现此概念有迥然不同的含义。这些含义能大大增强我们对中国为发展成为一个海洋大国所做出的努力的理解。这个概念是在中国有一个现代的海军或海军战略家之前由其他有影响力的大国为争夺亚太地区的影响力而发展起来的。如今, 中国对此概念的权威解释显示出其灵活性, 微妙性和多面性。这些解释特征恰恰能与北京在管理其海上崛起过程中许多有时是相互矛盾的因素相适应。这些因素包括由于不断增大距离和活动强度所导致的海上通道安全日益增长的重要性。